The term AMA/AMAN to designate plants : cultural heritage of the Amazon and the West Indies - (:unkn) unknown (My University, 2023)
There are linguistic and cultural similarities between Creole and certain populations in southern Benin, particularly those speaking Gungbe and Fongbe. Both territories are former colonies of France, characterised by multilingualism and multiculturalism. What's more, there is a similarity in endogenous healthcare practices involving the use of medicinal plants. Some plant designations are also identical, such as the term ‘"ama/aman".
Keywords: African Research